A glass fiber reinforced nylon 6 plug shell composite material and preparation method thereof

By adding specific raw materials to the nylon 6 plug shell composite material, using the combination and synergistic effect, the problem of insufficient heat resistance of nylon 6 is solved, achieving a wider application range and a longer service life.

CN118909431BActive Publication Date: 2025-04-15DONGGUAN JIAOYANG PLASTIC TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410872013.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-01
Publication Date
2025-04-15
Estimated Expiration
2044-07-01

AI Technical Summary

Technical Problem

Nylon 6 has poor heat resistance, which limits its application range in the field of charging pile plugs, especially in electric vehicle charging stations with high heat resistance requirements.

Method used

The glass fiber reinforced nylon 6 plug shell composite material is used to enhance the reinforcement effect of glass fiber on nylon 6 resin by adding raw materials such as polyester fiber, N-phenylmaleimide, polyvinyl alcohol, flame retardant, silica and zirconium dioxide.

Benefits of technology

It significantly improves the heat resistance, compression resistance and tensile resistance of the plug housing composite material, thereby broadening its application range in the field of charging pile plugs and extending the service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present application relates to the field of modified composite materials, and more specifically, it relates to a glass fiber reinforced nylon 6 plug shell composite material and a preparation method thereof. The glass fiber reinforced nylon 6 plug shell composite material is made of the following raw materials: glass fiber, nylon 6 resin, flame retardant, silicon dioxide, zirconium dioxide, polyester fiber, N-phenylmaleimide, and polyvinyl alcohol; its preparation process is: firstly, silicon dioxide and zirconium dioxide are subjected to high temperature treatment, then glass fiber, nylon 6 resin, polyester fiber, N-phenylmaleimide, and polyvinyl alcohol are heated and mixed to form a mixture A, then flame retardant, silicon dioxide and zirconium dioxide are added to the mixture A and heated and mixed to form a mixture B, and the mixture B is melt-extruded through a twin-screw extruder, granulated, and a glass fiber reinforced nylon 6 plug shell composite material is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of modified composite materials, and more specifically, to a glass fiber reinforced nylon 6 plug housing composite material and a preparation method thereof. Background Art

[0002] With the popularity of electric vehicles, electric vehicle charging stations will become the focus of the development of the automotive industry and the energy industry. Therefore, the development of charging supporting service facilities around new energy vehicles has also ushered in new development opportunities and challenges. Among them, nylon 66 resin has good mechanical properties and heat resistance, so it has been widely used in the field of charging pile plug shells.

[0003] However, due to the gradual increase in the price of nylon 66 resin, it has had a relatively large impact on the industry. In addition, because the process of synthesizing the core of nylon 66 resin is still monopolized by foreign countries, some companies will use nylon 6 to replace nylon 66. However, due to the poor heat resistance of nylon 6 itself, it can only be used in some places with low heat resistance requirements, which limits the development of the charging pile industry. Summary of the invention

[0004] In order to effectively improve the heat resistance of nylon 6 and expand the application scope of nylon 6 in charging pile plugs, the present application provides a glass fiber reinforced nylon 6 plug shell composite material and a preparation method thereof.

[0005] In a first aspect, the present application provides a glass fiber reinforced nylon 6 plug housing composite material, which adopts the following technical solution:

[0006] A glass fiber reinforced nylon 6 plug shell composite material, the glass fiber reinforced nylon 6 plug shell composite material comprises the following raw materials in parts by weight:

[0007] Glass fiber: 20-35 parts;

[0008] Nylon 6 resin: 25-45 parts;

[0009] Flame retardant: 1.2-2.6 parts;

[0010] Silicon dioxide: 3.5-6.5 parts;

[0011] Zirconium dioxide: 2.2-3.8 parts;

[0012] Polyester fiber: 7-15 parts;

[0013] N-phenylmaleimide: 9-16 parts;

[0014] Polyvinyl alcohol: 6 to 12 parts.

[0015] By adopting the above technical scheme, the compounding effect between polyester fiber, N-phenylmaleimide and polyvinyl alcohol is utilized to produce a further synergistic effect with silicon dioxide and zirconium dioxide, which can be beneficial to enhance the reinforcing effect of glass fiber on nylon 6 resin, effectively enhance the heat resistance of the plug shell composite material, and further achieve the purpose of improving the compressive performance, tensile performance and heat resistance of the plug shell composite material, thereby broadening the application scope of the plug shell composite material;

[0016] Among them, both polyester fiber and polyvinyl alcohol have good ductility, and through the cross-linking effect of N-phenylmaleimide on nylon 6 molecular chains, a three-dimensional network structure with better ductility can be formed on the surface of nylon 6 molecular chains, and the glass fiber is covered by the three-dimensional network structure on the surface of nylon 6 molecular chains, so that the strength of the glass fiber and nylon 6 molecular chains when combined can be effectively improved. In addition, by utilizing the good compatibility between silica and zirconium dioxide and nylon 6 resin, the surfaces of silica and zirconium dioxide can be better polymerized with the three-dimensional network structure on the surface of nylon 6 molecular chains under the synergistic effect of polyester fiber and polyvinyl alcohol, so as to further fill the three-dimensional network structure on the surface of nylon 6 molecular chains, thereby better enhancing the connection stability of glass fiber on the surface of nylon 6 molecular chains, and achieving the purpose of simultaneously improving the mechanical properties and heat resistance of the plug shell composite material.

[0017] Preferably, the glass fiber reinforced nylon 6 plug housing composite material comprises the following raw materials in parts by weight:

[0018] Glass fiber: 25-30 parts;

[0019] Nylon 6 resin: 33-38 parts;

[0020] Flame retardant: 1.7-2.2 parts;

[0021] Silicon dioxide: 4.5-5.5 parts;

[0022] Zirconium dioxide: 2.8-3.4 parts;

[0023] Polyester fiber: 10-12 parts;

[0024] N-phenylmaleimide: 12-14 parts;

[0025] Polyvinyl alcohol: 8 to 10 parts.

[0026] By adopting the above technical scheme, by controlling the addition amount of each raw material to a certain range, it can be obviously found that the Shore D hardness value and stress value of the surface of the plug shell composite material are effectively improved, and at the same time, the stress value difference obtained by testing the surface of the plug shell composite material after heating is also more effectively reduced, which can reflect that the heat resistance and various mechanical properties of the surface of the plug shell composite material are further improved.

[0027] Preferably, both the silicon dioxide and zirconium dioxide are nanometer-sized.

[0028] By adopting the above technical scheme, by controlling the particle size range of silica and zirconium dioxide at the nanometer level, the synergistic effect between silica and zirconium dioxide and polyester fiber, N-phenylmaleimide and polyvinyl alcohol in the system can be further enhanced, so that the three-dimensional network structure strength of the molecular chain surface of nylon 6 resin is further improved, thereby achieving the purpose of more effectively improving the compressive performance, tensile performance and heat resistance of the plug shell composite material of the present application, thereby extending the service life of the plug shell composite material to a certain extent.

[0029] Preferably, the softening point of the polyester fiber is 150-180°C.

[0030] Preferably, the molecular weight of the polyvinyl alcohol is 120,000 to 150,000.

[0031] By adopting the above technical solution and selecting polyester fibers and polyvinyl alcohol with specific parameters, the compounding effect of the two in the solution can be further optimized, thereby better improving the compressive properties, tensile properties and heat resistance of the plug shell composite material of the present application.

[0032] Preferably, the raw material further comprises dimethylformamide, and the weight ratio of the N-phenylmaleimide to dimethylformamide is (2-3):1.

[0033] By adopting the above technical scheme, by adding dimethylformamide to the raw material system and controlling the weight ratio of dimethylformamide to N-phenylmaleimide, the uniformity of N-phenylmaleimide in the system can be effectively improved, thereby facilitating the cross-linking degree of N-phenylmaleimide on the nylon 6 molecular chain, thereby achieving the purpose of further enhancing the mechanical properties and heat resistance of the plug shell composite material.

[0034] Preferably, the surface roughness Ra of the glass fiber is 80-90 μm.

[0035] By adopting the above technical solution, after the surface roughness of the glass fiber is controlled within a certain range, the contact area between the glass fiber and the nylon 6 resin can be increased, thereby better improving the bonding strength between the glass fiber and the nylon 6 molecular chain, thereby achieving the purpose of further improving the compressive resistance, tensile resistance and heat resistance of the plug shell composite material of the present application.

[0036] Preferably, the raw materials further include 1.6 to 3 parts by weight of tert-butyl perbenzoate.

[0037] By adopting the above technical solution, after adding tert-butyl perbenzoate, the activity of N-phenylmaleimide in the system can be more effectively improved, so that the degree of crosslinking between N-phenylmaleimide and nylon 6 resin is further improved.

[0038] Preferably, the flame retardant is one or both of ammonium pyrophosphate and ammonium polyphosphate.

[0039] By adopting the above technical solution and selecting a specific flame retardant, the stress value difference of the surface of the plug shell composite material of the present application obtained by testing before and after heating can be better reduced, thereby further improving the stability of the plug shell composite material at high temperatures.

[0040] In a second aspect, the present application provides a preparation process of a glass fiber reinforced nylon 6 plug housing composite material, comprising the following steps:

[0041] Weigh glass fiber, nylon 6 resin, polyester fiber, N-phenylmaleimide, polyvinyl alcohol, flame retardant, silicon dioxide and zirconium dioxide according to weight;

[0042] The silicon dioxide and zirconium dioxide are subjected to high temperature treatment and then used for later use;

[0043] Glass fiber, nylon 6 resin, polyester fiber, N-phenylmaleimide and polyvinyl alcohol are heated, mixed and stirred to form a mixture A;

[0044] Adding the flame retardant and the silicon dioxide and zirconium dioxide that have been subjected to high temperature treatment to the mixture A, mixing and stirring at a constant temperature to form a mixture B;

[0045] The mixture B is melt-extruded through a twin-screw extruder and granulated to obtain a glass fiber reinforced nylon 6 plug housing composite material.

[0046] By adopting the above process steps to prepare the glass fiber reinforced nylon 6 plug shell composite material, the synergistic effect between polyester fiber, N-phenylmaleimide and polyvinyl alcohol can be better exerted, so that it can be more conducive to enhancing the adhesion of glass fiber to nylon 6 molecular chain, so as to improve the overall mechanical properties and heat resistance of the surface of the plug shell composite material after molding, so as to achieve the purpose of effectively broadening the application scope of the plug shell composite material.

[0047] In summary, this application has the following beneficial effects:

[0048] 1. By utilizing the compounding effect between polyester fiber, N-phenylmaleimide and polyvinyl alcohol, a further synergistic effect with silicon dioxide and zirconium dioxide is produced, which can help to enhance the reinforcing effect of glass fiber on nylon 6 resin, effectively enhancing the heat resistance of the plug shell composite material, and further achieving the purpose of improving the compressive performance, tensile performance and heat resistance of the plug shell composite material, thereby broadening the application scope of the plug shell composite material;

[0049] 2. By adding dimethylformamide to the raw material system and controlling the weight ratio of dimethylformamide to N-phenylmaleimide, the uniformity of N-phenylmaleimide in the system can be effectively improved, thereby facilitating the cross-linking degree of N-phenylmaleimide on the nylon 6 molecular chain, thereby further enhancing the mechanical properties and heat resistance of the plug shell composite material;

[0050] 3. By adopting the above process steps to prepare the glass fiber reinforced nylon 6 plug shell composite material, the synergistic effect between polyester fiber, N-phenylmaleimide and polyvinyl alcohol can be better exerted, which can be more conducive to enhancing the adhesion of glass fiber to nylon 6 molecular chain, so as to improve the overall mechanical properties and heat resistance of the surface of the plug shell composite material after molding, so as to achieve the purpose of effectively broadening the application scope of the plug shell composite material. DETAILED DESCRIPTION

[0051] The present application is further described in detail below in combination with embodiments and comparative examples.

[0052] Example

[0053] Examples 1-3

[0054] A glass fiber reinforced nylon 6 plug shell composite material is prepared by the following steps:

[0055] Step 1: Weigh 20 g of glass fiber, 45 g of nylon 6 resin, 7 g of polyester fiber, 9 g of N-phenylmaleimide, 12 g of polyvinyl alcohol, 1.2 g of brominated epoxy resin, 3.5 g of silicon dioxide and 3.8 g of zirconium dioxide according to weight;

[0056] Step 2: Place silicon dioxide and zirconium dioxide in a high-temperature calcining furnace at 800°C for high-temperature treatment and set aside;

[0057] Step 3: Place glass fiber, nylon 6 resin, polyester fiber, N-phenylmaleimide, and polyvinyl alcohol in a high viscosity mixer, heat to 260° C., and mix and stir for 15 minutes to form a mixture A;

[0058] Step 4: Add the brominated epoxy resin and the high-temperature treated silicon dioxide and zirconium dioxide to the mixture A in the high-viscosity mixer, and mix and stir at a constant temperature of 260° C. for 20 minutes to form a mixture B;

[0059] Step 5: Melt and extrude the mixture B through a twin-screw extruder, and granulate it to obtain a glass fiber reinforced nylon 6 plug housing composite material.

[0060] Wherein, in Example 1, the temperatures of zones 1-10 of the twin-screw extruder are: 215°C, 225°C, 235°C, 230°C, 237°C, 235°C, 228°C, 240°C, 245°C, 250°C, the die temperature is 270°C, and the material residence time is 30s;

[0061] The surface roughness Ra of glass fiber is 30-40μm; the particle size of silicon dioxide is 5μm; the particle size of zirconium dioxide is 6μm; the softening point of polyester fiber is 230-240℃, and the molecular weight is 180,000 to 200,000; the molecular weight of polyvinyl alcohol is 160,000 to 180,000; the CAS number of N-phenylmaleimide is 941-69-5.

[0062] Example 2

[0063] The difference between Example 2 and Example 1 is that, in this example, in step 1, 35 g of glass fiber, 25 g of nylon 6 resin, 15 g of polyester fiber, 16 g of N-phenylmaleimide, 6 g of polyvinyl alcohol, 2.6 g of brominated epoxy resin, 6.5 g of silicon dioxide and 2.2 g of zirconium dioxide are weighed by weight.

[0064] Example 3

[0065] The difference between Example 3 and Example 1 is that, in this example, in step 1, 25 g of glass fiber, 38 g of nylon 6 resin, 10 g of polyester fiber, 14 g of N-phenylmaleimide, 8 g of polyvinyl alcohol, 1.7 g of brominated epoxy resin, 5.5 g of silicon dioxide and 2.8 g of zirconium dioxide are weighed by weight.

[0066] Example 4

[0067] The difference between Example 4 and Example 1 is that, in this example, in step 1, 30 g of glass fiber, 33 g of nylon 6 resin, 12 g of polyester fiber, 12 g of N-phenylmaleimide, 10 g of polyvinyl alcohol, 2.2 g of brominated epoxy resin, 4.5 g of silicon dioxide and 3.4 g of zirconium dioxide are weighed by weight.

[0068] Example 5

[0069] The difference between Example 5 and Example 1 is that, in this example, the particle size of silicon dioxide is 70 nm; the particle size of zirconium dioxide is 80 nm;

[0070] Example 6

[0071] The difference between Example 6 and Example 1 is that in this example, the softening point of the polyester fiber is 150-180°C.

[0072] Example 7

[0073] The difference between Example 7 and Example 1 is that in this example, the molecular weight of polyvinyl alcohol is 120,000 to 150,000.

[0074] Example 8

[0075] The difference between Example 8 and Example 1 is that in this example, the raw material also includes dimethylformamide, and in step 3, 4.5 g of dimethylformamide is added together; wherein the CAS number of dimethylformamide is 68-12-2.

[0076] Example 9

[0077] The difference between Example 9 and Example 1 is that in this example, the raw material also includes dimethylformamide, and in step 3, 3 g of dimethylformamide is added; wherein the CAS number of dimethylformamide is 68-12-2.

[0078] Example 10

[0079] The difference between Example 10 and Example 9 is that in this example, the raw materials also include tert-butyl perbenzoate, and in step three, 3 g of tert-butyl perbenzoate is added together; wherein the CAS number of tert-butyl perbenzoate is 614-45-9.

[0080] Embodiment 11

[0081] The difference between Example 11 and Example 9 is that in this example, the raw materials also include tert-butyl perbenzoate, and in step three, 1.6 g of tert-butyl perbenzoate is added together; wherein the CAS number of tert-butyl perbenzoate is 614-45-9.

[0082] Example 12

[0083] The difference between Example 12 and Example 1 is that in this example, the surface roughness Ra of the glass fiber is 80-90 μm.

[0084] Example 13

[0085] The difference between Example 13 and Example 1 is that, in this example, the brominated epoxy resin is replaced by an equal amount of ammonium pyrophosphate.

[0086] Embodiment 14

[0087] The difference between Example 14 and Example 1 is that, in this example, the brominated epoxy resin is replaced by equal amounts of ammonium pyrophosphate and ammonium polyphosphate; wherein the ammonium pyrophosphate and ammonium polyphosphate are added in equal proportions.

[0088] Comparative Example

[0089] Comparative Example 1

[0090] A glass fiber reinforced nylon 6 plug housing composite material, which differs from Example 1 in that the polyester fiber is replaced by an equal amount of polybutylene terephthalate fiber.

[0091] Comparative Example 2

[0092] A glass fiber reinforced nylon 6 plug housing composite material, which differs from Example 1 in that N-phenylmaleimide is replaced by an equal amount of N-arylmaleimide.

[0093] Comparative Example 3

[0094] A glass fiber reinforced nylon 6 plug housing composite material, which differs from Example 1 in that polyvinyl alcohol is replaced by an equal amount of polyethylene glycol.

[0095] Comparative Example 4

[0096] A glass fiber reinforced nylon 6 plug shell composite material, which differs from Example 1 in that polyester fiber is replaced by an equal amount of polybutylene terephthalate fiber, N-phenylmaleimide is replaced by an equal amount of N-arylmaleimide, and polyvinyl alcohol is replaced by an equal amount of polyethylene glycol.

[0097] Performance testing

[0098] Mechanical properties 1: GB / T 38119-2019 "Test of Shore Hardness Tester" was used to detect the surface Shore D hardness values ​​of the samples made of the glass fiber reinforced nylon 6 plug housing composite materials prepared in Examples 1-14 and Comparative Examples 1-4. A total of 5 points of the sample were measured and the average value was calculated; among them, the higher the Shore D hardness value of the sample surface, the stronger the compressive resistance.

[0099] Mechanical properties 2: The tensile strength of the glass fiber reinforced nylon 6 plug housing composite material samples prepared by Examples 1-14 and Comparative Examples 1-4 at room temperature and pressure was tested using "GB / T 1040.1-2006 Determination of tensile properties of plastics". The samples were fixed on a universal testing machine, and a tensile force was applied at a constant speed until the sample broke. The stress value of the universal testing machine was recorded and denoted as a1. Among them, the larger the value of a1, the stronger the tensile resistance.

[0100] Heat resistance: The tensile strength of the glass fiber reinforced nylon 6 plug housing composite material samples prepared by Examples 1-14 and Comparative Examples 1-4 at 140°C was tested using GB / T 1040.1-2006 Determination of tensile properties of plastics. The samples were placed in a high-temperature furnace and heated to 140°C and then fixed on a universal testing machine. A tensile force was applied at a constant speed until the sample broke, and the stress data of the universal testing machine was recorded as a2. The difference between a1 and a2 was calculated and recorded as R. The smaller R was, the stronger the heat resistance was.

[0101] Table 1 - Summary of test data of Examples 1-14 and Comparative Examples 1-4

[0102]

[0103]

[0104] According to the comparison of the test data of Example 1 and Comparative Examples 1-4 in Table 1, it can be seen that when the inventors simultaneously add polyester fiber, N-phenylmaleimide and polyvinyl alcohol to the raw material system, the synergistic cooperation between the three can be utilized, which can effectively increase the Shore D hardness value and tensile strength of the surface of the plug shell composite material, and at the same time, it can also be beneficial to improve its tensile strength difference at high temperature, thereby clearly reflecting that the mechanical properties and heat resistance of the surface of the plug shell composite material are more effectively enhanced, which is convenient to broaden the application scope of the plug shell composite material to a certain extent.

[0105] According to the comparison of the test data of Examples 1-4 in Table 1, it can be seen that when the inventor controls the addition amount of each raw material component to a certain value, the heat resistance, compression resistance and tensile resistance of the surface of the plug shell composite material can be better enhanced, thereby being able to more effectively extend the service life of the plug shell composite material.

[0106] According to the comparison of the test data of Examples 1, 5-7 and 12 in Table 1, it can be seen that when the inventor controls the different physical parameters of silica, zirconium dioxide, polyester fiber, polyvinyl alcohol and glass fiber in the system, it can be beneficial to improve the compressive strength and tensile strength of the plug shell composite material of the present application measured at room temperature and pressure, and at the same time, it can effectively reduce the change value of the tensile strength of the plug shell composite material before and after heating, thereby achieving the purpose of simultaneously enhancing the mechanical properties and heat resistance of the plug shell composite material of the present application.

[0107] According to the comparison of the test data of Examples 1 and 8-9 in Table 1, it can be seen that when the inventors add a certain mass of dimethylformamide to the raw material system, the synergistic effect of polyester fiber, N-phenylmaleimide and polyvinyl alcohol in the system can be better exerted, thereby being able to further effectively improve the Shore D hardness value and tensile strength of the plug shell composite material, while also being able to better reduce the difference in tensile strength of the plug shell composite material before and after heating, thereby achieving the purpose of enhancing the overall mechanical properties and heat resistance of the surface of the plug shell composite material.

[0108] According to the comparison of the test data of Examples 9-11 in Table 1, it can be seen that when the inventors add a certain mass of tert-butyl perbenzoate, it is beneficial to better enhance the compounding effect between dimethylformamide and N-phenylmaleimide, so as to further enhance the synergistic effect between N-phenylmaleimide and polyester fiber and polyvinyl alcohol in the raw material system, thereby further improving the compressive resistance, tensile resistance and heat resistance of the surface of the plug shell composite material, so as to reduce the surface damage of the plug shell composite material of the present application when used in different environments, thereby affecting the charging safety.

[0109] According to the comparison of the test data of Examples 1 and 13-14 in Table 1, it can be seen that when the inventors choose ammonium pyrophosphate to replace the brominated epoxy resin, it can be more conducive to improving the compressive strength and tensile strength of the plug shell composite material measured at room temperature and pressure, and at the same time can effectively reduce the change value of the tensile strength of the plug shell composite material before and after heating, which is conducive to further improving the mechanical stability of the plug shell composite material of the present application when used in different environments, and then can better extend the service life of the plug shell composite material, so as to achieve the purpose of broadening the application scope of the existing plug shell composite material, and has great economic value.

[0110] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A glass fiber reinforced PA6 plug shell composite material, characterized in that: The glass fiber reinforced PA6 plug housing composite material comprises the following raw materials in parts by weight: Glass fiber: 20~35 parts; PA6 resin: 25~45 parts; Flame retardant: 1.2~2.6 parts; Silicon dioxide: 3.5~6.5 parts; Zirconium dioxide: 2.2~3.8 parts; Polyester fiber: 7~15 parts; N-phenylmaleimide: 9-16 parts; Polyvinyl alcohol: 6-12 parts.

2. The glass fiber reinforced PA6 plug housing composite material according to claim 1, characterized in that: The glass fiber reinforced PA6 plug housing composite material comprises the following raw materials in parts by weight: Glass fiber: 25~30 parts; PA6 resin: 33~38 parts; Flame retardant: 1.7~2.2 parts; Silicon dioxide: 4.5-5.5 parts; Zirconium dioxide: 2.8~3.4 parts; Polyester fiber: 10~12 parts; N-phenylmaleimide: 12-14 parts; Polyvinyl alcohol: 8-10 parts.

3. A glass fiber reinforced PA6 plug housing composite material according to any one of claims 1-2, characterized in that: The silicon dioxide and zirconium dioxide are both nanometer-level.

4. A glass fiber reinforced PA6 plug housing composite material according to any one of claims 1-2, characterized in that: The softening point of the polyester fiber is 150-180°C.

5. A glass fiber reinforced PA6 plug housing composite material according to any one of claims 1-2, characterized in that: The molecular weight of the polyvinyl alcohol is 120,000 to 150,000.

6. A glass fiber reinforced PA6 plug housing composite material according to any one of claims 1-2, characterized in that: The raw materials also include dimethylformamide, and the weight ratio of the N-phenylmaleimide to dimethylformamide is (2-3):

1.

7. The glass fiber reinforced PA6 plug housing composite material according to claim 6, characterized in that: The raw materials also include 1.6 to 3 parts by weight of tert-butyl perbenzoate.

8. A glass fiber reinforced PA6 plug housing composite material according to any one of claims 1-2, characterized in that: The surface roughness Ra of the glass fiber is 80-90 μm.

9. A glass fiber reinforced PA6 plug housing composite material according to any one of claims 1-2, characterized in that: The flame retardant is one or both of ammonium pyrophosphate and ammonium polyphosphate.

10. A process for preparing a glass fiber reinforced PA6 plug shell composite material, used for preparing a glass fiber reinforced PA6 plug shell composite material according to any one of claims 1 to 9, characterized in that: The following steps are involved: Weigh glass fiber, PA6 resin, polyester fiber, N-phenylmaleimide, polyvinyl alcohol, flame retardant, silicon dioxide and zirconium dioxide according to weight; The silicon dioxide and zirconium dioxide are subjected to high temperature treatment and then used for later use; Glass fiber, PA6 resin, polyester fiber, N-phenylmaleimide and polyvinyl alcohol are heated, mixed and stirred to form a mixture A; Adding the flame retardant and the silicon dioxide and zirconium dioxide that have been subjected to high temperature treatment to the mixture A, mixing and stirring at a constant temperature to form a mixture B; The mixture B was melt-extruded through a twin-screw extruder and granulated to obtain a glass fiber reinforced PA6 plug housing composite material.

Citation Information

Patent Citations

  • Halogen-based flame-retardant glass fiber-reinforced polyamide resin composition, and method for preparing same

    CN104854192A

  • Glass fiber board or section or pipe and forming method

    CN106009613A